The role of users in a continuous development ERP strategy: An analysis on the impact of end-users in the creation of an ERP continuous development strategy - Gonçalves, R.; Rocha, D.; Lopes da Costa, R.; Pereira, L.; Dias, Á.; Teixeira, N. (International Journal of Procurement Management, 2023)
The ERP projects are one of the best strategies to increase efficiency in organisations, however companies can face big deviations regarding budget and time. To enhance the likelihood for a successful implementation, organisations must establish a long-term continuous development plan that creates a technological environment that prioritises users as positive agents of change. Pre-implementation and implementation phases gather key stakeholders and system experts while the post-implementation phase is traditionally neglected in an ERP project framework which leads to inefficient long-term strategies. System users are key pieces when defining an ERP long-term strategic plan. This research was focused on understanding the role that end-users play in the continuous development of an ERP project. The study concluded that an appropriate technological environment would lead to more participative and involved user and the ability to understand the special impact of end-users will enhance the chances for a better implemented and less costly system.